Orthodontic-surgical treatment of a patient with Marfan Syndrome and Obstructive Sleep Apnea Syndrome: a case report with a 9-year follow-up - RODRIGUES,Willian Caetano (2019)
ABSTRACT Marfan’s (MFS) syndrome is characterized by a defect in the connective tissue, which affects multiple organic systems. Therefore, the management of these patients requires a multidisciplinary approach. This case reports the orthodontic-surgical treatment of a patient who presented both Marfan’s and obstructive sleep apnea syndrome. Patient had malocclusion, TMJ clicking, vertical maxillary excess, mandibular retrognathia, severe esthetic compromise, signs and symptoms of obstructive sleep apnea syndrome, as well as alterationsin joints, cardiovascular and respiratory systems. He was treated with bimaxillary surgery aimed to enhance esthetics, occlusion and address the obstructive sleep apnea syndrome. The clinical results show that a desirable functional occlusion was achieved and both patient’s facial esthetics and quality of life were significantly improved. After a 9-year follow-up period, these pleasing features were maintained. The diagnosis and management of Marfan’s patients is challenging and require multidisciplinary follow-up.